ANALYSIS OF THE INFLUENCE OF REYNOLDS NUMBER AND MAXIMUM THICKNESS ON AN AERODYNAMIC PROFILE (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Aerodynamics is the science that studies the influence of the gas movements over solid bodies. This branch of science has been target of much interest mainly because of the large use of aircrafts and auto-vehicles nowadays. Using a numerical simulation software, this paper proposes a study on the influence of Reynolds number and maximum thickness of an airfoil on the aerodynamic forces. Stall angle, Lift and Drag forces were evaluated on different conditions. Lift and Drag coefficients in function of the angle of attack were obtained numerically and compared with experimental data from literature. The results showed that the software is able to simulate the main variables that influence the aerodynamics of NACA profiles with limitations. Keywords: Lift, Drag, NACA profile, Aerodynamics, XFLR5